Training of health science professors to support the education of high-ability university students - Flores-Bravo, Juan Francisco; Rodríguez-Naveiras, Elena; Valadez Sierra, María de los Dolores; Costantini, Dylan; Borges, África (Frontiers in Education, 2024)
The objective of this study was to evaluate the impact and satisfaction of a course-workshop offered to university professors for the educational attention of students with high abilities, which is based on a critical need that has been neglected; the training of teachers to attend to this type of students. In this context, it is essential to implement programs that demystify high abilities and provide teachers with effective tools to inspire and challenge these students. For this purpose, a mixed methodology was used; in the quantitative part, two approaches were combined: a quasi-experimental design with a nonequivalent control group, and a pre-experimental design. In the qualitative part, the content of openended questions was analyzed. Quantitative results show significant differences in the interaction and timing of the intervention in the experimental group (p=0.000). Likewise, a positive level of achievement and approval was observed in each of the subjects taught, obtaining an average of 41.12 out of 47 total points. In addition, a satisfactory evaluation of the course-workshop offered was reported, since 95.2% said that they agreed fairly or strongly agreed with the contents, 96.8% agreed fairly or strongly agreed with the didactic material, and 90.47% rated the performance of the instructors as excellent. The lexical analysis yielded three classes in relation to the most significant learning acquired during the course, while the comments and suggestions for improvement were grouped into four classes. The findings of this study highlight the importance of developing teacher training programs based on a clear understanding of high abilities and allow expanding knowledge in this field of study.